Ameliorating the antitumor activity of lenalidomide using PLGA nanoparticles for the treatment of multiple myeloma - Veera Venkata Satyanarayana Reddy Karri; Nagasamy Venkatesh Dhandapani; Sai Sandeep Mannemala; Kollipara Radhakrishna; Shashank Mulukutla; Dedeepya Sudunagunta (Universidade de São Paulo, 2017)
Abstract Lenalidomide (LND) is an anti-cancer drug and an effective derivative of thalidomide used for multiple myeloma therapy. Because of its poor solubility in water, LND is known to cause low oral bioavailability (below 33%), and as a direct consequence of this, the dosing frequency is extended thus increasing risk of toxicity. To improve its bioavailability and sustained release, the present study aims to formulate polymeric nanoparticles (NPs) for LND using [Poly (lactic-co-glycolic acid)] (PLGA) as a polymer. The polymeric NPs were evaluated for particle size, SEM, XRD, drug content, entrapment efficiency (EE), in vitro release studies and in vivo bioavailability studies in rats. The formulated NPs possessed a size of 179±0.9 nm and a zeta potential of -24.4 ± 0.2 mV. The drug loading and EE of the optimized formulation was 32 ± 0.37 % and 78 ± 0.92% respectively. After oral administration of LND PLGA-NPs, the relative bioavailability was enhanced about 3.67-fold compared to LND. This study demonstrates the novel drug delivery for LND with PLGA-NPs as effective drug delivery system for sustained delivery of LND.